Awareness, attitude and practice of family planning methods in a tertiary care hospital, Uttar Pradesh, India - Jahan, Uruj; Verma, Kavita; Gupta, Shruti; Gupta, Renu; Mahour, Simmi; Kirti, Neha; Verma, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Family planning services have the potential to improve the quality of the lives of people and their economic welfare. The objective of the study was to assess the level of awareness, attitude, and current practice of different family planning methods and to elicit reasons for couples not using any method. Methods: A cross sectional descriptive study was done among 1050 married women of reproductive age . Results: Most of the women were between 21-34 years of age (60.1%) and had primary level of education (40%).It was observed that with increase in level of education, awareness also increased (77.7%). The most common source of information was mass media (53.2%). Contraceptive prevalence rate was 62.9%, higher than the national data as 28.5%. Most of them (93.1%) were aware of atleast one family planning method. The most commonly known were OCPs (74.8%), condom (68.8%) and IUCD (56.6%). Awareness about female sterilisation (36.4%) was more than male sterilisation (25.3%). 62.9% had used atleast one contraceptive method, three prevailing methods used were condom (65.1%), OCPs (31.8%) and IUCD (9.09%). Reasons precluding women from practicing contraception were desire to have a child (60.5%), lack of knowledge (42.4%), and unbearable side effects (25.5%). Majority (92.4%) thought that contraceptive use was beneficial but only (27.2%) expressed the willingness to start practicing contraception if they received more information about the subject. Conclusions: Majority of women had optimal knowledge and favourable attitude, still there is need to educate and motivate couples to improve family planning services.